2011
DOI: 10.1038/bmt.2010.325
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism of IL-17 gene in the recipient is associated with acute GVHD after HLA-matched unrelated BMT

Abstract: IL-17 has an important role in the host defense against extracellular pathogens and the pathophysiology of autoimmune diseases. This study retrospectively examined the impact of a single-nucleotide polymorphism (rs2275913, G197A) in the IL-17 gene of a total 510 recipients with hematologic malignancies and their unrelated donors on the clinical outcomes in HLAmatched myeloablative (discovery study) and nonmyeloablative (validation study) BMT through the Japan Marrow Donor Program (JMDP). In the discovery study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Previous studies showed association between G197A polymorphism and several chronic diseases [12], like ulcerative colitis [19] and rheumatoid arthritis [20]. A study reported association between allele A of IL17A polymorphism and high risk of cGVHD [12]. Until now, no other work was reported in the literature relating IL17F polymorphism and GVHD.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies showed association between G197A polymorphism and several chronic diseases [12], like ulcerative colitis [19] and rheumatoid arthritis [20]. A study reported association between allele A of IL17A polymorphism and high risk of cGVHD [12]. Until now, no other work was reported in the literature relating IL17F polymorphism and GVHD.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have been devoted to analyze the role of IL-17, a new discovered cytokine, in the pathogenesis of GVHD [12,[16][17][18]. However, this is the first work that evaluated both cytokines IL-17A and IL17F, involving the genetic and phenotypic aspects, and investigated the immunophenotypic aspect of IL-17A regarding systemic cGVHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been devoted to analyze the role of IL-17, a new discovered cytokine, in the pathogenesis of GVHD [12, 1618]. However, this is the first work that evaluated both cytokines IL-17A and IL17F, involving the genetic and phenotypic aspects, and investigated the immunophenotypic aspect of IL-17A regarding systemic cGVHD.…”
Section: Discussionmentioning
confidence: 99%